KEWENANGAN PERADILAN TIPIKOR PASCA BERLAKUNYA UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - Mohammad Sahlan (Arena Hukum, 2016)
Abstract Â The purpose of this journal is to analyze the competency of the administrative court and the corruption court to examine and decide the element of abused of power in corruption act after enacment of the Government Administration Acts and the legal implication when the legislation policy provides the authority to examine and decide upon the matter to the two institutions court, and the arrangements to ideal concept in the future. This is a normative law research, using conceptual approach, statute approach and case approach. The result of this research shows that theoretically and practically the concept of "abuse of power" in the Government Administration Acts is the same with the concept of "abuse of power" in the Eradication Corruption Acts. Therefore, the corruption court and administrative court both have absolute competence to examine and decide abuse of power in corruption. However, based on the principle of "lex posteriori derogate legi priori", the authority to examine and decide the element of abuse of power as positions in corruption becomes the absolute competence of the administrative court. Legal implications of the policy legislation give authority to both courts to examine and decide the abuse of power. First, potential competency disputes between both court; Second, create uncertainty mechanism for handling abuse of power in the corruption thus hampering efforts to eradicate corruption. Regulation in the future as problems of abuse of power as position does not dispute between the administrative court and the corruption court on judicial competency: First, the equation perspectives on the applicability of the Government Administration Acts, of the assessment of abuse of power in corruption. Second, reaffirming the absolute competence of the administrative court as arranged in the Government Administration Acts of assessment substance abuse of power in Article 3 of the Eradication Corruption Acts and arrangement in handling mechanisms (procedural law).Â Abstrak Jurnal ini bertujuan mengkaji kewenangan Peradilan TUN dan Peradilan Tipikor dalam memeriksa dan memutus unsur menyalahgunakan kewenangan dalam Tipikor pasca lahirnya UU Administrasi Pemerintahan, implikasi hukumnya ketika kebijakan legislasi memberikan kewenangan untuk memeriksa dan memutus masalah tersebut kepada dua lembaga Peradilan, serta konsep pengaturannya ke depan yang ideal. Kajian ini merupakan kajian hukum normatif, dengan menggunakan conceptual approach, statute approach, dan case approach. Hasil kajian menunjukkan secara teoritis dan praktis konsep â€œpenyalahgunaan wewenangâ€ dalam UU Administrasi Pemerintahan sama dengan konsep â€œmenyalahgunakan kewenanganâ€ dalam UU Pemberantasan Tipikor. Karenanya, Peradilan Tipikor dan Peradilan TUN secara atributif sama-sama memiliki kompetensi absolut untuk memeriksa dan memutus penyalahgunaan kewenangan dalam Tipikor. Namun demikian, berdasarkan asas â€œlex posteriori derogate legi prioriâ€, kewenangan untuk memeriksa dan memutus unsur penyalahgunaan kewenangan karena jabatan dalam Tipikor menjadi kompetensi absolut Peradilan TUN. Implikasi hukum kebijakan legislasi yang memberikan kewenangan untuk memeriksa dan memutus penyalahgunaan kewenangan dalam Tipikor kepada dua lembaga peradilan, Pertama, berpotensi menimbulkan sengketa kewenangan mengadili antara kedua peradilan tersebut; Kedua, menimbulkan ketidakpastian mekanisme penanganan penyalahgunaan kewenangan dalam Tipikor sehingga menghambat upaya pemberantasan Tipikor. Pengaturan ke depan agar masalah penyalahgunaan kewenangan karena jabatan tidak menjadi sengketa kewenangan mengadili antara Peradilan Tipikor dan Peradilan TUN: Pertama, penyamaan perspektif mengenai keberlakuan UU Administrasi Pemerintahan, terhadap penilaian penyalahgunaan kewenangan dalam Tipikor. Kedua, menegaskan kompetensi absolut Peradilan TUN yang diatur dalam UU Administrasi Pemerintahan terhadap penilaian unsur penyalahgunaan kewenangan dalam Pasal 3 UU Pemberantasan Tipikor dan melakukan penataan pada mekanisme penangannya (hukum acara).